Bias or Reality: Rethinking of Halal Tourism in Indonesia - Muhammad, M; Bachri, Syabbul; Husnaini, M (KARSA Journal of Social and Islamic Culture, 2022)
Lately, the term halal or sharia has become a trend in Indonesia caused that the term is identical to Islam and most Indonesian citizens are Muslim. Besides being a weapon to sell commodities on the market, halal labels are also used to promote tourism resorts. Indonesian Council of Religious Scholars (MUI) issues fatwa to regulate halal tourism and has the authority to issue halal tourism certificates. This study addresses academic anxiety, whether tourism that has received a halal certificate following the MUI fatwa is natural halal tourism or it is only a formality of marketing bias. This article uses the field study method that results from direct observation and literature study to ascertain the meaning of halal. The study results showed that no tourism in Indonesia deserves a halal label even though it has obtained a halal certificate from the MUI. It is observed that in many tourism locations, disobedience and neglect occur. The term halalis a tourist object limited to marketing bias and is not confirmed in the field.